Outcomes of a Teaching Learning Sequence on Modelling Surface Phenomena in Liquids - Onofrio Rosario Battaglia; Aurelio Agliolo Gallitto; Giulia Termini; Claudio Fazio (MDPI AG, 2023)
In this paper we discuss the effects of modelling and computer simulation activities in promoting student use of lines of reasoning useful to explain proposed or observed situations. The activities are part of a structured Teaching/Learning Sequence on surface phenomena in liquids. We outline a model of liquid based on a mesoscopic approach, examples of computer simulations students can use during the activities, and we describe the Teaching/Learning Sequence. During the pedagogical activities, students can simulate the liquid behaviour by controlling many simulation parameters, such as the interaction intensity among liquid and solid particles. The results of the analysis of student answers to a questionnaire before and after instruction, and of other qualitative data, show that these activities can help the students to think in terms of "mechanisms of functioning".